Acoustic wave propagation model in the surface layer area based on the Runge-Kutta method - Defrianto, Defrianto; Wirianto, Hazmi; Malik, Usman (Science, Technology and Communication Journal, 2023)
Simulation of acoustic wave propagation in the surface layer area is carried out by taking a positive value acoustic velocity gradient so that in this simulation there will be a wave phenomenon trapped in the surface layer area. In this study, acoustic beam emission was conducted by varying the angle of incidence and length of the beam used, and the determination of the acoustic velocity gradient was carried out using the Runge-Kutta order of order 2. The results showed that at depths of 0 to 40 meters with an acoustic velocity of 1405 m/s, for a length of 1 meter and a gradient pattern of +2.5 obtained a minimum angle of incidence of 0.09 radians with a wave propagation of 250 meters. Comparison between analytical and computational results on wave propagation in the surface layer area is a 4.51% error.